Experimental Manufacturing Methods of Glass Fiber Composites Considering Flexural Behaviour - Wipada Boransan; Thongchart Kerdphol; Veena Phunpeng (Spektrum Industri, 2021)
Fiber-reinforced plastic laminates (FRPL) and sandwich composites are outstanding materials due to its mechanical properties (i.e., light weight, low density and high strength to weight ratio). These applications are widely used in the fields of aviation, automotive and construction industries. The superior mechanical properties depend on the properties of reinforcing materials, matrixes and manufacturing processes. This research proposes the comprehensive study of mechanical properties of epoxy resin reinforced by glass fibers under different processes. Glass-fiber sandwich composites were manufactured by the hand lay-up process and cured in different methods (i.e., with and without vacuum bagging). The comparison between curing temperature and pressure is investigated using the vacuum bagging process to determine the mechanical properties under flexural tests. Experimental tests are performed using the universal testing machine (UTM). As a result, it is confirmed that the hand lay-up process affects the flexural stress, deflection and internal force of both fiber-reinforced plastic laminates and sandwich composites. At the high curing temperature, the vacuum bagging method significantly provides the greater flexural stress, deflection and load